Brittle Shear Failure Prevention of a Non-ductile RC Column using Glass Fiber Reinforced Polymer (GFRP). (2015) - Rodsin, Kittipoom
Abstract: The objective of the research is to improve the seismic behaviour of a non-ductile column failing in a brittle shear using glass fiber-reinforced polymer (GFRP). Two non-ductile columns with similar size, concrete and cross-sectional properties were tested under lateral cyclic loading. The first column (G1) possesses longitudinal reinforcement ratio of 2.76% with 0.25x0.35m in size and 1.1 m in height. The minimum requirement for the amount of stirrup was used in these columns. For the second column (G2), the column was wrapped by 3-layer GFRP 500 mm from the base. When column G1 was subjected to lateral cyclic loading, the column failed in shear at the lateral drift of 3.5%. For column G2, the GFRP could increase column shear capacity and also confine the concrete in the plastic hinge region. Consequently, the column maximum displacement was dramatically increased up to 12% drift and the column eventually failed in flexure mode associated with longitudinal reinforcement yielding, compression bar buckling and crushing of concrete inside the GFRP. It is evident that the GFRP could effectively improve the unfavourable column shear failure of non-ductile columns by increasing column shear strength and concrete ductility in the plastic hinge region.